Tools and good practices for software quality insurance under skilful methodologies - Mercado-Ramos, Victor Hugo; Zapata, Julián; Ceballos, Yony Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The quality management in companies engaged in software development projects, provides a competitive advantage by guaranteeing that their products are high quality made. Skilful methodologies emerge for the application in projects whose nature is changing or where it is necessary to get a quick investment return. Organizations that choose to shift to skilful methodologies face challenges like ensuring the quality not only of the product but the product and the project. Models such as the Capability Maturity Model Integration and ISO 25010, are known and work well in traditional development environments. For skilful methodologies, there are some less popular proposals, including the Test Driven Development, Continuous Integration and Product Backlog Rating metrics. Nevertheless, although the literature reported good results, these are not sufficiently documented to be used in any skilful project. This paper analyzes the proposals aimed at improving the quality of products made with skilful methodologies, tools and best practices, and gives a series of recommendations for quality management in software projects.